FAKTOR-FAKTOR PENYEBAB KENAKALAN REMAJA (STUDI KASUS PENGGUNA NARKOBA DI DESA PERUMNAS SIMALINGKAR KECAMATAN PANCUR BATU) - Rio LF Hutabarat (Welfare StatE, 2013)
Juvenile comes from the latin word is adolensence which means to grow or grow into adulthood. The term adolensence has the meaning which more broadly includes the maturity of mental, emotional, social and physical abuse between the ages of 11 or 12 years up to 20 years. Juvenile delinquency is an act that violates the norms, rules or laws in a society that is done at the age of adolescence or transition period for both children and adults. Acts of uncontrolled juvenile delinquency will lead a teenager on behavior of juvenile crime which is one of social ills. One form of juvenile delinquency, which is currently highly developed teen drug users. This research aims to find out what are the factors the causes of teenagers become drug users in Simalingkar village of Perumnas is expected to provide information and knowledge about juvenile delinquency so that it can reduce the social causes of juvenile delinquency problems particularly drug. This research is a descriptive qualitative approach using of case studies. The unit of analysis is the study of teenage drug users, their families and the community in the village of Perumnas Simalingkar. Given the number of units of analysis of the data, then it's pretty much taken the few that served as the source of the informant informant key to those involved directly in drug use drug users totaled 6 people and additional informants to those who can provide information although not directly against drug use data collection techniques used in this research is a technique of collecting data obtained in the study through the primary data (observation, and interviews) and secondary data (study library). Based on the results of data analysis that is done can be known that teenagers in the village of Perumnas Simalingkar using drugs since they are sitting on the bench elementary school. Teens using drugs because of the influence of the environment and the teammates who tend to behave as well as distorted understanding is very minimal will harm from drugs. The family of the teen drug users in the village of Perumnas Simalingkar less may give attention, affection, and it's in teens so that teenagers tend to behave according to their wishes, without anyone ignore what they do. Keywords : Adolescent, Juvenile delinquency, Drug